Airway management considerations in children with I-cell disease. Issue 5 (May 2015) - Mallen, Jonathan; Highstein, Mallory; Smith, Lee; Cheng, Jeffrey
Abstract Inclusion-cell disease (mucolipidosis II/I-cell disease) is a lysosomal storage disease characterized by a constellation of physical findings which complicate airway management. There is currently a deficit of published literature describing appropriate strategies for acute management of these children's airways. This paper details emergency and anesthetic airway management concerns and potential solutions in a small series of children with I-cell disease.